2013
DOI: 10.1021/ac403274a
|View full text |Cite
|
Sign up to set email alerts
|

Results of an Interlaboratory Comparison of Analytical Methods for Contaminants of Emerging Concern in Water

Abstract: An evaluation of existing analytical methods used to measure contaminants of emerging concern (CECs) was performed through an interlaboratory comparison involving 25 research and commercial laboratories. In total, 52 methods were used in the single-blind study to determine method accuracy and comparability for 22 target compounds, including pharmaceuticals, personal care products, and steroid hormones, all at ng/L levels in surface and drinking water. Method biases ranged from <10% to well over 100% in both ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Interlaboratory agreement for targeted chemical analyses using environmental samples can range from single digit to more than 50% RSD, depending on the analyte, matrix and measured concentration (Vanderford et al, 2014). It should be noted that the present study addresses only the reproducibility of bioassay responses since a single laboratory collected and processed all the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Interlaboratory agreement for targeted chemical analyses using environmental samples can range from single digit to more than 50% RSD, depending on the analyte, matrix and measured concentration (Vanderford et al, 2014). It should be noted that the present study addresses only the reproducibility of bioassay responses since a single laboratory collected and processed all the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the issue of assay performance was also examined using a round robin validation process in Europe for a number of chemicals, including BPA, which identified that some laboratories were able to accurately assay BPA and other chemicals without contamination, while other laboratories were unable to assay BPA or other chemicals accurately (Vanderford et al, 2014). …”
Section: Routes and Sources Of Bpa Exposure: Is Assay Contaminatiomentioning
confidence: 99%
“…Considering the high degree of temporal [18] and geographical [19] variability, high-throughput time-sensitive analytical screening methods would greatly advance the resolution of environmental monitoring. Also, considering the variability of methods currently used for TOrC analyses [20], the reproducibility and accuracy of the data must be enhanced by introducing automation into the entire analytical procedure.…”
Section: Introductionmentioning
confidence: 99%